2016
DOI: 10.1155/2016/8163474
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Obesity Affect Lipid Profile in the Salivary Glands

Abstract: In today's world wrong nutritional habits together with a low level of physical activity have given rise to the development of obesity and its comorbidity, insulin resistance. More specifically, many researches indicate that lipids are vitally involved in the onset of a peripheral tissue (e.g., skeletal muscle, heart, and liver) insulin resistance. Moreover, it seems that diabetes can also induce changes in respect of lipid composition of both the salivary glands and saliva. However, judging by the number of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 31 publications
4
45
0
1
Order By: Relevance
“…After 8 weeks of the study we observed a 30% increase in body weight, a nearly 100% increase in insulin content, and a 70% increase in the concentration of glucose. We also noted that HFD led to IR, as confirmed by 200% increase in HOMA-IR, which is consistent with our results as well as those of other researchers [6,16,19,42,43].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…After 8 weeks of the study we observed a 30% increase in body weight, a nearly 100% increase in insulin content, and a 70% increase in the concentration of glucose. We also noted that HFD led to IR, as confirmed by 200% increase in HOMA-IR, which is consistent with our results as well as those of other researchers [6,16,19,42,43].…”
Section: Discussionsupporting
confidence: 94%
“…Lipid accumulation has also been observed in salivary glands. Matczuk et al [6] showed that IR induced by chronic feeding with high-fat diet results in altered lipid fractions of salivary glands. These changes were expressed differently depending on the salivary gland type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, children with ECC have high levels of proinflammatory cytokines [7], which trigger a cascade of inflammatory processes [8] associated with impaired growth and obesity inducing mechanisms [9]. Obesity and stunting also cause changes in the salivary glands and the composition of saliva, which increases the risk for ECC by lowering salivary pH [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have observed a steady growth in the frequency of overweight and obesity, observed not only among adults, but also children and adolescents [2]. This results from various genetic, environmental and economic (easy access to cheap and highly calorific food) factors as well as evolutionary conditioning (sedentary lifestyle, low physical activity, low energy expenditure) [1,3]. According to the latest WHO report, nearly 41 million children under 5 years of age are overweight or obese [4].…”
Section: Introductionmentioning
confidence: 99%